2017
DOI: 10.1038/s41535-017-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of graphene quantum dots

Abstract: Graphene quantum dots with the high edge-to-area ratio have possibly substantial spin polarized edge states, which theoretically can generate fascinating magnetic properties. The magnetism of well-defined graphene quantum dots is relevant with both fundamental physics and potential applications in spintronics. In this article, we report the intrinsic magnetism of graphene quantum dots. Our graphene quantum dots with the average diameter of ca. 2.04 nm show the purely Curie-like paramagnetism with the local mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 50 publications
3
52
0
2
Order By: Relevance
“…To perform the theoretical study, it was considered CQDs exhibiting the following features: quasi‐spherical morphology with diameters in the range of 1.2‐2.8 nm (AFM), presence of stacked graphitic layers, as well as of disordered carbon (Powder X‐ray Diffraction (PXRD), Raman), presence of oxygenated functional groups (FTIR), and elemental composition typical of CQDs synthesized from CA . Previous studies in the literature have suggested that CQDs are composed of stacked graphene nanoflakes (all layers with same diameter or layers with varying diameter), with functional groups attached to external surface. It was used this relatively simplified picture to create more realistic atomic configurations, exhibiting the observed characteristics in the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…To perform the theoretical study, it was considered CQDs exhibiting the following features: quasi‐spherical morphology with diameters in the range of 1.2‐2.8 nm (AFM), presence of stacked graphitic layers, as well as of disordered carbon (Powder X‐ray Diffraction (PXRD), Raman), presence of oxygenated functional groups (FTIR), and elemental composition typical of CQDs synthesized from CA . Previous studies in the literature have suggested that CQDs are composed of stacked graphene nanoflakes (all layers with same diameter or layers with varying diameter), with functional groups attached to external surface. It was used this relatively simplified picture to create more realistic atomic configurations, exhibiting the observed characteristics in the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The bond lengths 10C‐7C and 7C‐3C are with same values 1.412 Å in the more stable triplet ground state than the same corresponding length 10C‐7C (1.422 Å) and 7C‐3C (1.40 Å) in singlet ground state. These can be attributed to the stability of the FM structure as well as confirm that the shapes and edges which depends on the bond lengths and angles in the benzene ring affect magnetism in triangulene like other GQDs . Figure presents the optimized structures of triangulene with four transition metals.…”
Section: Resultsmentioning
confidence: 99%
“…We applied (2) to fit data shown in Figure 4 , and pure GQD (curve c, data factorized with factor 800), respectively. It was shown by Sun et al [27] that pure GQDs demonstrate diamagnetic and paramagnetic properties at low temperature. In their case, the magnetization curve measured at 2 K demonstrated a saturation effect, and it was fit with high accuracy by (1) where the value of the fitting parameter J was about 0.5, that is, with high accuracy equal to the electron spin angular momentum.…”
Section: Resultsmentioning
confidence: 99%